2015
DOI: 10.18632/oncotarget.5012
|View full text |Cite
|
Sign up to set email alerts
|

MiR-497 suppresses angiogenesis and metastasis of hepatocellular carcinoma by inhibiting VEGFA and AEG-1

Abstract: Hepatocellular carcinoma (HCC) is a worldwide malignance and displays marked vascular abnormalities and active metastasis. MicroRNAs (miRNAs) have been shown to play important roles in regulating tumor properties in cancer, however, whether miR-497 contributes to HCC angiogenesis or metastasis remains unclear. In this study, we found that miR-497 was significantly down-regulated in HCC tissue samples and cell lines. Gain-of-function and loss-of-function studies revealed that miR-497 could repress both the pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 32 publications
3
71
0
Order By: Relevance
“…miR-497 and miR-195 belong to miR-15 family, It has been reported that miR-497∼195 negatively regulates angiogenesis in tumours21222324. Almeida et al .…”
Section: Discussionmentioning
confidence: 99%
“…miR-497 and miR-195 belong to miR-15 family, It has been reported that miR-497∼195 negatively regulates angiogenesis in tumours21222324. Almeida et al .…”
Section: Discussionmentioning
confidence: 99%
“…57 Beside promoting resistance to imatinib in chronic myeloid leukemia 36 and promoting resistance to gefitinib in non-small cell lung cancer, 35 FGF2 expression is also a stronger predictor of paclitaxel resistance than P-gp, p53 or Bcl-2 in several cancers. 58 Several VEGFA-/FGF2-targeting miRNAs have been described in different cancers, including miR-503 in prostate cancer, 59 miR-497 in hepatocellular carcinoma 60 and miR-185 in clear cell renal cell carcinoma. 61 Here we present data indicating that miR-205 targets VEGFA and FGF2 in breast cancer cells leading to decreased activity of PI3K/AKT signaling pathway, increased apoptosis and restoration of drug sensitivity in drug-resistant breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miRNAs has been reported to both activate and inhibit tumor progression [7]. For example, previous studies have demonstrated the dysregulation of miR-495 in multiple types of cancers, including pancreatic cancer [8], ovarian cancer [9], renal cancer [10], gastric cancer [11], hepatocellular cancer [12], and gallbladder cancer [13]. Furthermore, overexpression of miR-495 inhibits tumor progression by inducing G0/G1 cell cycle arrest [9] and by suppressing angiogenesis and metastasis [12].…”
Section: Introductionmentioning
confidence: 99%